Tameng Keberlangsungan Organisasi: Sisi Gelap Creative Accounting - Angelia, Gebriela Christina; Jurana, Jurana; Saleh, Fadli Moh; Paranoan, Selmita (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2024)
Abstract: Shielding Organizational Sustainability: The Dark Side of Creative AccountingPurpose: To understand the meaning of student perceptions regarding Creative Accounting practices in student activity units.Method: Qualitative method with a phenomenological approach.Results: There are three meanings of student perceptions about Creative Accounting practices. First, students consider the practice of Creative Accounting to be unethical behavior. Second, Creative Accounting functions as a strategy passed down from generation to generation. Third, Creative Accounting practices are interpreted as a shield for organizational sustainability.Novelty: Conceptualization of three meanings of Creative Accounting practices.Contribution: Research on Creative Accounting shows that if a mistake is made repeatedly it will become a normal behavior to do.   Abstrak: Tameng Keberlangsungan Organisasi: Sisi Gelap Creative AccountingTujuan: Untuk memahami makna dari persepsi mahasiswa terkait praktik Creative Accounting pada unit kegiatan mahasiswa.Metode: Metode kualitatif dengan pendekatan fenomenologi.Hasil: Terdapat tiga makna dari persepsi mahasiswa tentang praktik Creative Accounting. Pertama, mahasiswa menganggap praktik Creative Accounting merupakan suatu perilaku yang tidak etis. Kedua, fungsi Creative Accounting sebagai strategi turun temurun. Ketiga, praktik Creative Accounting dimaknai sebagai tameng demi keberlangsungan organisasi.Kebaruan: Terkonsepnya tiga makna atas praktik Creative Accounting.Kontribusi: Dari penelitian tentang Creative Accounting memperlihatkan bahwa sebuah kesalahan jika dilakukan berulang-ulang maka akan menjadi sebuah perilaku yang wajar saja untuk dilakukan.